The Influence of Job Stress towards Employee Negative Behavior with Self-Esteem as the Moderator and Mediator - Septian, Ecsan B1024141007 (Jurnal Manajemen Update, 2019)
ABSTRACTEmployee negative behavior is one of the most problems that inflict a loss which been found in an organization or firm worldwide. The cause of this global issue has been traced down by researchers for decades and it leads to the well documented direct effect of job stress on negative behavior. However, the previous theoritical explanation and empirical findings of the relationship has been inconsistent with the level of negative behavior. This inconsistency brings a question whether negative behavior is only caused by job stress, which in several research found that there is a possibility of the internal attitude of self as another trigger. This study aims to examine the relationship between job stress, employee negative behavior, and negative self esteem, also to explore the moderation effect of negative self esteem on the relationship between job stress and employee negative behavior. Using sampling method, 100 questionnaires have been collected from eligible samples in the area of Pontianak, Indonesia. SmartPLS 3.0 was used for Structural Equation Model Partial Least Square (SEMPLS) analysis to test the validity, reliability, and hypotheses in this research. The study found that there is a postitive relationship between job stress and employee negative behavior, job stress and negative self esteem, and negative self esteem and employee negative behavior. This study also found that negative self esteem has the positive impact towards the influence of job stress and employee negative behavior.  Keyword : Job stress, Employee negative behavior, Negative self esteem, Moderating effect, SEMPLS References Afshar, A.F., & Alishahi, A.G. (2015). The role of concientiousness on job stress and deviant work behavior : the variable share of perceived organizational support. Indian Journal of Fundamental and Applied Life Sciences, Vol. 5 (S3), pp. 226-231.Al Fayyad, M. (2015). Validating Typology of Robinson and Bennett (TRB) of Deviant Workplace Behavior (DWB) in Jordanian Industrial Sector in Zarqa City (JISZC). Journal of Business Studies Quarterly, Volume 6, Number 4.Balakrishnamurti, C. & Shankar, S. (2009). Impact of age and level of experience on occupational stress experienced by non-gazetted officers of the central reserve police force. Industrial Psychiatri Journal, 18(2), 81-83Baumeister, R. F., Campbell, J. D., Krueger, J. I., & Vohs, K. D. (2003). Does high self-esteem cause better performance, interpersonal success, happiness, or healthier lifestyles?. Psychological Science in the Public Interest, 4, 1-44.Celik, K. (2013). The Effect of Role Ambiguity and Role Conflict on Performance of Vice Principals : the Mediating Role of Burnout. Egitim Arastirmalari-Eurasian Journal of Educational Research, 51, 195-214.Cooper, C.L., Marshall, J. (1978). Understanding Executive Stress. London, LN: The Macmillan Press LTD.Ferris, D.L., Keeping, L.M., Brown, D.J., & Lian, H. (2009). When Does Self-Esteem Relate to Deviant Behavior? The Role of Contingencies of Self-Worth. Journal of Applied Psychology, Vol. 94, No. 5, 1345–1353.Fox, S., & Spector, P.E. (2015). The Many Roles of Control in a Stressor-Emotion Theory of Counterproductive Work Behavior In Employee Health, Coping and Methodologies. Research in Occupational Stress and Well Being, Volume 5, 171–201.Gray-Little, B., Williams, V.S.L., & Hancock, T.D. (1997). An item response theory analysis of the Rosenberg Self-Esteem Scale. Personality and Social Psychology Bulletin, 23, 443-451.Jerusalem, M., & Schwarzer, R. (1989). Anxiety and Self esteem as Antecedents of Stress and Coping : a Longitudinal Study with German and Turkish Adolescent. Person.  indirid.  Diff.,  Vol.  10.  No.  7,  pp.  785-792.Kania, S.K. (2014) . The Relationship Between Gender Differences and Stress. The Huron University College Journal of Learning and Motivation, Vol. 52 : Iss. 1 , Article 7King, M. (2011). HR: Your Friend or Foe?. Retrieved from https://www.theguardian.com/money/2011/may/28/hr-friend-or-foe-human-resourcesLee, J.S., Joo, E.J., & Choi, K.S. (2012). Perceived Stress and Self-esteem Mediate the Effects of Work-related Stress on Depression. Wiley Online Library (wileyonlinelibrary.com) DOI: 10.1002/smi.2428.Lee, K.J., Suh, C.H., Kim, J.E., & Park J.O. (2016). The impact of long working hours on psychosocial stress response among white-collar workers. Ind Health, 55(1), 46–53.Lyf, M. (2016). Understand Self [PowerPoint Slides]. Retrieved from https://www.slideshare.net/mickylyf/understand-self-63653956MacDonald, W. (2006). The impact of job demands and workload on stress and fatigue. Australian Psychologist Journal, 38(2), 102-117Mayfield, C.O., & Taber, T.D. (2009). A prosocial self-concept approach to understanding organizational citizenship behavior. Journal of Managerial Psychology, Vol. 25 No. 7, pp. 741-763.Mcdaniel, M.A., & Whelpley, C.E. (2014). Self esteem and counterproductive behavior:A meta-analytic review.Chicago, IL.Penney, L.M., & Spector, P.E. (2005). Job stress, incivility, and counterproductive work behavior (CWB): the moderating role of negative affectivity. Journal of Organizational Behavior, 26, 777–796.Purnomo, W. (2016). Mengelola Tekanan Bagi Salespeople. Retrieved from http://www.wahyu-purnomo.com/mengelola-tekanan-bagi-salespeopleRosenberg, M. (1965). Society and the adolescent self-image. Princeton, NJ: Princeton University Press.Sohail, M. & Rehman, C.A. (2015). Stress and Health at the Workplace-A Review of the Literature. Journal of Business Studies Quarterly, Volume 6, Number 3.Sunday, A.J. (2014). The causes and impart of deviant behavior in the workplace. American Journal of Social Sciences, Arts, and Literature, Vol.1, No. 2, pp. 1-11.The American Psychological Association. (2011). Stress and Gender. Retrieved from https://www.apa.org/news/press/releases/stress/2011/gender.pdfVokic, N.P., & Bogdanic A. (2008). Individual Differences and Occupational Stress Perceived: A Croatian Survey. Zagreb International Review of Economics & Business, Vol. 11, No. 1, pp.61-79.Wilder, J. (2017). Stop Worrying About Failures. Focus on Mindset. Retrieved from https://medium.com/the-mission/stop-worrying-about-failure-focus-on-mindset-110b81f3e7b6Yan, H.Y., Ying, Y.F., Yong, X.G., & Li, Y. (2014). Leadership, work stress and employee behavior. Chinese Management Studies, Vol. 8 Iss 1 pp. 109 – 126.